Sicily from Aeneas to Augustus : new approaches in archaeology and history (New perspectives in the ancient world, 2000)
This volume provides a chronological account of the island's history, interwoven with discussions of Sicilian identity, to show Sicily as a centre of affairs within the context of a fundamentally regional ancient world